Surface displacements, deformations and gravity changes due to underground heat source - BRIMICH, Ladislav; KOHÚT, Igor (Contributions to Geophysics and Geodesy, 2018)
Thermo-elastic strains and stresses play a considerable role in the stress state of the lithosphere and its dynamics, especially at pronounced positive geothermal anomalies. Topography has a significant effect on ground deformation. Two methods for including the topographic effects in the thermo-viscoelastic model are described. First we use an approximate methodology which assumes that the main effect of topography is due to the distance from the source to the free surface and permits to have an analytical solution very attractive for solving the inverse problem. A numerical solution (for 2D plain strain case) is also computed using finite element method (FEM). The numerical method allows to include the local shape of the topography in the modeling. In the numerical model the buried magmatic body is represented by a finite volume thermal source. The temperature distribution is computed by the higher-degree FEM. For analytical as well as numerical model solution only the forces of thermal origin are considered. The results show that for the volcanic areas with prominent topography, its effect on the perturbation of the thermo-viscoelastic solution (deformation and total gravity anomaly) can be quite significant. In consequence, neglecting the topography could give erroneous results in the estimated source parameters.